Role and Effective Therapeutic Target of Gut Microbiota in Heart Failure - Qiujin Jia; Hao Li; Huan Zhou; Xiaonan Zhang; Ao Zhang; Yingyu Xie; Yanyang Li; Shichao Lv; Junping Zhang (Cardiovascular Therapeutics)
Although the mechanism of the occurrence and development of heart failure has been continuously explored in the past ten years, the mortality and readmission rate of heart failure is still very high. Modern studies have shown that gut microbiota is associated with a variety of cardiovascular diseases, among which the study of gut microbiota and heart failure attracts particular attention. Therefore, understanding the role of gut microbiota in the occurrence and development of heart failure will help us further understand the pathogenesis of heart failure and provide new ideas for its treatment. This paper introduced intestinal flora and its metabolites, summarized the changes of intestinal flora in patients with heart failure, clarified that intestinal barrier damage and bacterial translocation induced inflammation and immune response aggravated heart failure, and altered intestinal microflora affected various metabolic pathways including trimethylamine/TMAO, SCFA, and Bile acid pathway leads to heart failure. At the same time, regulating intestinal microflora through diet, probiotics, antibiotics, fecal transplantation and microbial enzyme inhibitors has grown up to be a potential treatment for many metabolic disorders.